Pengaruh Penggunaan Media Video Animasi Pembelajaran IPS terhadap Hasil Belajar - Pratiwi, Hana Eka; Budiaman, B; Safitri, Desy (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The results of this research aim to determine the effect of using social media animation video media on learning outcomes. The method used is a quantitative method in a True Experimental approach with a Posttest Only Control Design. The sampling technique in this research used simple random sampling with samples of class VIII A and VIII B. Both samples were given a post test after being given treatment in the form of learning using animated videos in class VIII A and power point media in class VIII B. The results showed that there were the effect of the use of animated social studies learning video media on student learning outcomes. This can be seen from the results of hypothesis testing using the Mann-Whitney test which produces a significance value (2-tailed) of 0.000 (p < 0.05).